AB0490 Evaluation of inhibitory factor of radiographic progression by iguratimod add-on therapy in rheumatoid arthritis patients with inadequate responses to disease-modifying anti-rheumatic drugs. (12th June 2018) - Katayama, K.; Kon, Y.; Okubo, T.; Fukai, R.; Makino, Y.; Ito, H.
Abstract : Background: Iguratimod (IGU) is one of csDMARDs (Conventional synthetic Disease modified anti-rheumatoid arthritis drug) for RA patients in Japan. It was reported to suppress the production of inflammatory cytokines by inhibiting NFkB pass-way. IGU add-on therapy was efficient in patients with RA who were previously designated MTX-monotherapy inadequate responders (MTX-IR). The efficacy of IGU add-on therapy in bDMARDs (Biological DMARD)-IR patients was also reported. In this study, we showed disease activity and safety, and showed also radiographic evaluation for the first time by adding IGU. Objectives: To obtain DAS28-ESR and adverse event data about adding IGU on RA patients with poor response to csDMRADs and/or bDMARDs in single-centre, open label and retrospective study. Furthermore, to show the radiological evaluation after one year. Methods: Clinical and radiographic efficacy was assessed by disease activity score of 28 joints (DAS28) ESR (n=68) and the modified total Sharp score (mTSS) (n=44), respectively. We evaluated which factors are important in determining a prognosis of clinical response and mTSS. For safety, adverse events (AE) were investigated on all patients (n=89). Results: 89 RA patients were recruited, and male was 28% (n=25). Mean age was 61.5 years old and mean of disease duration was 87 months. Main csDMARDs were MTX (72%). The mean dose of MTX was 7 mg/week (The average dose in Japan). Observational period was 13 months (range, 1 to 30). DAS28-ESR changed from 4.3±1.1 to 3.6±1.2 after adding IGU for 6 months (p<0.0001). The relation with the predictive factors before treatment and the response by using Iguratimod. CRP, ESR, swelling joint, DAS28-ESR, CDAI and VAS at the baseline were all significantly high in Response (good response+ moderate response) group than No-response group (table 1). Yearly mTSS was 0.60 and rate of structural remission (mTSS ≤0.5) was 87%. Rapid radiological progression was not seen even if yearly mTSS at the baseline was 5.52. The relation between yearly mTSS and disease duration was shown in Figure (r=0.33, p=0.029). Adverse AE were observed such as transaminase elevation, stomatitis and dizziness. All AE was not serious. DAS28-ESR, CRP, ESR and swelling joint were prognostic factors of the group of good and moderate response against no response group. Conclusions: Adding IGU to csDMARDs with poor response in RA patients is effective, but AE should be considered. Radiographic progression by Iguratimod might be inhibited in early phase of RA. Disclosure of Interest: None declared